THE EFFECTIVENESS OF MODEL ELICITING ACTIVITIES TOWARD MATHEMATICS LEARNING OUTCOMES - Muha Dyah Peta Balla Sari; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Learning based on the group after the students were given Worksheets Students, the teacher will provide problems then described and carried out by teachers in front of the class. It makes the students working on the issue by way of the teacher to face a new problem of students having difficulty in the settlement. The learning model is required that can enhance student learning outcomes by using Model Eliciting Activities. This research aims to know the effectiveness of Model Eliciting Activities against the learning outcomes of students of grade VIII Junior High School (SMP) Muhammadiyah Boarding School (MBS) Prambanan even semester academic year 2017/2018. This research using quantitative research methods. The population used is grade VIII SMP MBS academic year of 2017/2018. The sample used, i.e., class VIII E and VIII F. Data collection techniques used is the test. The instrument used was a pretest and posttest. The data analysis technique used is a prerequisite test analysis and hypothesis testing. The results of research on a significant level of 5% and degrees of freedom = 63 shows; (1) there is a difference in learning outcomes of students using Model Eliciting Activities (MEAs) with learning outcomes of students who use conventional learning model class VIII even semester of SMP MBS Prambanan academic year of 2017/2018. (2) Model Eliciting Activities (MEAs) is more effective than the conventional model against learning outcomes of students of grade VIII, even semester of SMP MBS Prambanan academic year of 2017/2018.